A tripartite division of stative verbs in Turkish - Kısa Kaz, Nagihan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This thesis investigates the semantic and syntactic behavior of stative verbs in Turkish in the light of two recent analyses, namely Maienborn (2005, 2007) and Rothmayr (2009). It proposes a tripartite division for stative verbs in Turkish: (i) Kimian states (K-states), (ii) Davidsonian states (D-states), the distinction already drawn by Maienborn (2005, 2007) and (iii) Equivocal states (E-states). Evidence for this division comes from both the existing tools in the literature and new tools suggested in this study. In new tools, based on the (in)compatibility of stative verbs with two post-verbs -(y)Adur and -(y)Iver and two converbial suffixes forming adverbial clauses -(y)A…(y)A and -(A/I)r….-mAz, all of which convey certain aspectual information, the tripartite division of stative verbs in Turkish is further supported. It is argued that the distribution of -(y)Adur and -(y)A…(y)A in stative verbs indicates K-states/D-states division manifest itself in Turkish such that K-states are incompatible with both units, whereas D-states are compatible with them. On the other hand, the distribution of -(y)Iver and -(A/I)r….-mAz in stative verbs shows these units are incompatible with stative verbs under stative interpretation, which validates all the types are stative. A further type to this bipartite division is suggested, namely E-states, by showing E-states are likely to be ambiguous between stative and achievement reading. They can be disambiguated via adverbial use, and therefore are highly context-dependent. The equivocal nature of E-states shows itself especially when E-states occur with -(y)Iver and -(A/I)r….-mAz since E-states are compatible with both units, but only under an achievement reading.
Keywords: Turkish language -- Verb.